EVALUATION OF RELEASED TEF (ERAGROSTIS TEF [ZUCC.] TROTTER) VARIETIES AT SOUTHWESTERN PART OF ETHIOPIA - BELETE, TEGEGN (Innovare Journal of Agricultural Sciences, 2022)
Objective: The objective of the study was to evaluate performance and identify high yielding and stable variety for southwestern part Ethiopia and recommend identified varieties for large scale production. Experimental Materials: Eight nationally released tef varieties were included in the study. The materials were obtained from Debre Zeit Agricultural Research Center (DZARC). Design and Trial Management: The experiment was conducted during the 2019 main cropping season at six locations, namely: Melko, Gechi, Omonada, Kersa, Mana, and Gooma weredas of Southwestern Ethiopia. The trial was conducted using randomized complete block design with three replications at all locations under rain-fed conditions. Sowing was done manually. Spacing between plots was 1 m, whereas that between replications was 1.5 m and the total plot size was 2 m × 2 m. Seed rates were based on the recommendation which was 15 kg/ha. Result and Discussion: Analysis of variance revealed the presence of significant (P < 0.05) differences among eight tef varieties of traits of days to heading, days to maturity, plant height, panicle length, lodging index, above ground biomass, and grain yield across locations. This indicated the presence of performance variation among the tested varieties for grain yield and it is possible to identify high yielder varieties for possible use in these locations. Conclusion and Recommendation: In general, varieties Dagim and Kora were high yielding and stable across locations and variety Gibe, Tesfa, and Negus were stable and low yielders across locations. The high yielding and stable varieties were recommendable for large scale production in southwestern part of Ethiopia. The experiment used data collected for only one season, which may limit the strength of its recommendation. However, the results are crucial in directing the breeding decision following additional season evaluation of the varieties in the same locations.